Improving Dysgraphia Writing Ability through Drill Method - Hanifah, Hasna Nur; Prayitno, Harun Joko (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine the effectiveness of the drill method in improving the writing skills of first-grade students at SDN Duwet 01 Baki who experience dysgraphia. Dysgraphia is a writing disorder that affects motor skills, writing speed, neatness, and students' independence. The drill method was chosen due to its repetitive practice-based approach, which gradually helps students build their writing skills. This study employs a qualitative descriptive method with Johnny Saldana's data analysis model. The research subjects consisted of 20 first-grade students and a class teacher. Data collection techniques included observation, interviews, and documentation to understand the drill method's implementation in-depth. The findings indicate that the drill method significantly enhances students' writing abilities, particularly in motor coordination, writing speed, letter consistency, and independence in completing writing tasks. Furthermore, this method increases students' motivation and confidence in writing. The implications of this study highlight the importance of the drill method as an alternative intervention in writing instruction for students with learning difficulties such as dysgraphia. Additionally, this study recommends integrating technology into the drill method to enhance the effectiveness of writing exercises more innovatively and engagingly for students.